(3cfR GdHjGfs - (3CHh YHO Gddg dSGf GdOjf eMeO Hf YHO Gddg Hf SYjO GHf GdNWjH GdZQfGWi GdCfOdSj,J (B776 (3g` s
(3ChdgG (B:s
(3CYde CjgG GdeSJQTO Cf ceGd GdEfSGfjI GdSGej, GdOQL dG Edi MO eYbhd, EfeG jchf eG jchf efg HJbhjI GdeRjJjf GddJjf HgeG cGf dfhY GdEfSGf GdSdWGf Ydi GdCQV s
(3BNQgG (B:s
(3eSJMbkG dUfYJg Cf Cf jSei aUjMkG HdjZkG jbGd aj gPG gh GdHjGf GdPj Ydeg GdQMef s
(3HgG fXGe GdJYbjHIs
(3gfGc Tc aj fSHI GdeNWhW ddeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B156 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs